Evolutionary Dynamics of Globalization - Naci Canpolat; Hüseyin Ozel (Turkish Economic Association, 2008)
The expansion of markets globalization was reversed during early 20th century and unfettered markets gave in to the welfare state and central planning. But the markets have been striking back since the early 1980s. Governments are withdrawn from economic activities, and many structural market reforms are implemented. Now the question is: Can the forces that market expansion create again reverse this expansion? This paper seeks an answer to this question by constructing an evolutionary game theoretical framework in which market and egalitarian societies appear as evolutionarily stable states and shows that catastrophic events such as the Great Depression can indeed cause switch over between evolutionarily stable states.
Keywords: B52; C73; 330; globalization; evolutionary game theory; evolutionarily stable states; behavioural strategies; Globalisierung; Evolutionäre Spieltheorie; Welt